Victimization features in traffic - Наглюк, Иван Сергеевич; Степанов, Алексей Викторович (Eastern-European Journal of Enterprise Technologies, 2012)
The processes of victimization in the area of traffic, taking into account the general provisions of victimological teaching are conceptually considered in present article